De Novo STX16 Deletions: An Infrequent Cause of Pseudohypoparathyroidism Type Ib that Should Be Excluded in Sporadic Cases - DEMİRCİOĞLU, SERAP (ENDOCRINE SOC, 2012)
Context: Maternally inherited 3-kb STX16 deletions cause autosomal dominant pseudohypoparathyroidism type Ib (PHP-Ib) characterized by PTH resistance with loss of methylation restricted to the GNAS exon A/B. Objective: The objective of the study was to search for the 3-kb STX16 deletion and to establish haplotypes for the GNAS region for two PHP-Ib patients and their families. Setting: The study was conducted at a research laboratory and tertiary care hospitals. Patients: The index cases presented at the ages 8 and 9.5 yr, respectively, with hypocalcemia, hyperphosphatemia, and elevated PTH. Interventions: There were no interventions. Results: DNA analyses of the index cases revealed an isolated loss of the GNAS exon A/B methylation and the 3-kb STX16 deletion. In the first family, the patient's healthy mother and sister showed no genetic or epigenetic abnormality, yet microsatellite analysis of the GNAS region indicated that both siblings share the same maternal allele, with the exception of an allelic loss for marker 261P9-CA1 (located within STX16), leading to the conclusion that a de novo mutation had occurred on the maternal allele. In the second family, three siblings of the index case are also affected, and an analysis of their DNA revealed the 3-kb STX16 deletion, which was also found in the healthy mother and a maternal uncle. Analysis of the siblings of the deceased maternal grandfather and some of their descendants excluded the 3-kb STX16 deletion, but haplotype analysis of the GNAS region suggested that he had acquired the mutation de novo. Conclusions: De novo 3-kb STX16 deletions, reported only once previously, are infrequent but should be excluded in all cases of PHP-Ib, even when the family history is negative for an inherited form of this disorder. (J Clin Endocrinol Metab 97: E2314-E2319, 2012)
Keywords: ALBRIGHTS HEREDITARY OSTEODYSTROPHY; PARATHYROID-HORMONE RESISTANCE; IMPRINTING CONTROL ELEMENT; GNAS LOCUS; AUTOSOMAL-DOMINANT; MOLECULAR DIAGNOSIS; EPIGENETIC DEFECTS; URIC-ACID; METHYLATION; REGION